2007
DOI: 10.2337/dc06-1399
|View full text |Cite
|
Sign up to set email alerts
|

Functional Vascular Endothelial Growth Factor −634G>C SNP Is Associated With Proliferative Diabetic Retinopathy

Abstract: OBJECTIVE -The purpose of this study was to evaluate the effect of the single nucleotide polymorphism (SNP) Ϫ634GϾC at the 5Ј regulatory region of the vascular endothelial growth factor (VEGF) in the risk of proliferative diabetic retinopathy (PDR) in the Brazilian population of European ancestry with type 2 diabetes. RESEARCH DESIGN AND METHODS-A case-control study was conducted in 501 type 2 diabetic patients of European ancestry. Patients underwent a standardized clinical, ophthalmological, and laboratory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
0
21
0
2
Order By: Relevance
“…Other gene polymorphisms in the RAGE gene 325 , the TGF-beta1 gene 326 , the VEGF gene [327][328][329][330] , the eNOS (endothelial nitric oxide synthase) gene 330 and vitamin D receptor 331 have also been associated with the presence or severity of DR from case-control studies. A meta-analysis that examined the association between DR in T2DM and polymorphisms in the gene for hyper-homocystinaemia (methylenetetrahydrofolate reductase, MTHFR) found only a marginal association with large heterogeneity between different studies 332 .…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Other gene polymorphisms in the RAGE gene 325 , the TGF-beta1 gene 326 , the VEGF gene [327][328][329][330] , the eNOS (endothelial nitric oxide synthase) gene 330 and vitamin D receptor 331 have also been associated with the presence or severity of DR from case-control studies. A meta-analysis that examined the association between DR in T2DM and polymorphisms in the gene for hyper-homocystinaemia (methylenetetrahydrofolate reductase, MTHFR) found only a marginal association with large heterogeneity between different studies 332 .…”
Section: Genetic Risk Factorsmentioning
confidence: 99%
“…Different origins of African-derived populations in the US and in Brazil or different proportions of admixture of the AfA population in Brazil could explain this. These data indicate the importance of analyzing EA and AfA separately in case-control studies, as we have already suggested (12). Moreover, the data suggest that these SNPs could represent valuable ancestry markers, which can be used to distinguish between chromosomal segments of subjects of AfA and EA.…”
Section: Adipor1 Snps In Brazilian Populations Of Different Ancestrymentioning
confidence: 83%
“…The reference group (control) consisted of 190 healthy DM2-free blood donor volunteers at HC-USP (96 EA and 94 AfA, age: 48.28 ± 16.39 years), who were previously described by Errera et al (11,12). The main clinical and laboratory data are reported in Table 1 and were obtained as recommended previously (11,12). A group of 439 non-diabetic quilombo remnant individuals was also included.…”
Section: Adipor1 Snps In Brazilian Populations Of Different Ancestrymentioning
confidence: 99%
See 1 more Smart Citation
“…1 206 ) являются продуктами одного гена, образующимися в результате альтернативного сплайсинга мРНК. В гене VEGF выявлены полиморфные позиции -634, +936, -2578; обнаружены взаимосвязи ва-риантов нуклеотидов в этих позициях с риском развития диабетической ретинопатии (ДР) в разных этнических группах [12][13][14][15]. По нашим данным [16,17], для больных СД 2 типа (СД2) свойственны комбинации гомозиготных вариантов VEGF 2578CC, 936CC, генов интерлейкинов и матриксных металлопротеиназ: IL4 590СС, IL6 174GG, IL10 592СC и 1082АА, TNFА 238GG, 308GG и 863СC, MMP-2 1306CC и ММР-9 1562СС.…”
Section: обоснование применения анти-Vegf терапии при дмоunclassified